WEWENANG PARTAI POLITIK DALAM MENENTUKAN CALON ANGGOTA DPR RI YANG LOLOS MENJADI ANGGOTA DPR RI (CONTOH KASUS PUTUSAN PENGADILAN NOMOR 520/PDT.SUS.PARPOL/2019/PN JKT.SEL) - Anindita Widyapradnya; Rasji rasji (Fakultas Hukum Universitas Tarumanagara, 2022)
Indonesia is a nation of law and a democratic country. With a massive population and area, thedemocracy is represented by a people’s representative body, like House of Representatives. Themember of the people’s representative is chosen by the people themselves through elections. Butusually there’s people who’s not agreed with the election’s result, like Mulan Jameela on 2019Legislative Elections. After she file a lawsuit to the South Jakarta District Court, Mulan Jameeladeclared to win the lawsuit according to Court Decision Number520/PDT.SUS/PARPOL/2019/PN.JKT.SEL and Gerindra Party is declared authorized to appointMulan Jameela as a member of House of Representatives. This caused two election participantswhich come from the same electoral district with Mulan Jameela, Ervin Luthfi dan Fahrul Rozi,dismissed for no apparent reason from the party so that Mulan Jameela could become a member ofHouse of Representative. The problem is how is the authority of political parties in determiningtheir cadres or members to qualify as members of the House of Representatives and the ef ect ofCourt Decision Number 520/PDT.SUS/PARPOL/2019/PN.JKT.SEL on the party's authority indetermining its cadres or members who qualify to become members of the House of Representativeof Indonesia Republic. This research is using the case approach method and statute approachmethod. The research results show that political parties are not authorized to determine whichcadres or its members qualify to become members of the House of Representative, and this courtdecision will not af ect the party's authority.